Newborn male presented with congenital diaphragmatic hernia and choledochal cyst: A case report - Daniel Krebs; Richard S. Herman; Christopher Blewett (Elsevier, 2015)
Infants with congenital diaphragmatic hernia (CDH) have an increased incidence of associated malformations, ranging from 10% to 50% higher than the general population [1-5]. Choedochal cysts, congenital cystic dilations of the biliary tree, are anomalies that have not yet been described in association with CDH. We describe a patient with a left congenital diaphragmatic hernia who was later diagnosed with a choledochal cyst.